Think in this way, then think in that way : imposing a switch between intuition and rationalization thinking approach for creative ideation - Bai, Shuming (2014)
This study investigated the impacts of different problem-solving approaches on creative ideation. In particular, the effects of intuition and rationalization on creativity, novelty and response utility were examined. Three hundred and twelve undergraduates (M age = 20.85 years, SD = 1.61) were randomly assigned to one of six experimental conditions: (1) Intuitive problem-solving approach only, (2) Rational problem-solving approach only, (3) Simultaneous intuitive and rational problem-solving approach, (4) Intuitive problem-solving approach then rational problem-solving approach, (5) Rational problem-solving approach then intuitive problem-solving approach and (6) Control (no experimental instructions), such that there were 52 participants exactly in each condition. All participants engaged in the same creative ideation task, where mood, motivation and typical thinking style were also measured. The results, under contrast analysis, demonstrated that the participants who were instructed to switch between intuition and rationalization scored significantly higher on the creative ideation task as compared to the counterparts who were instructed to think intuitively and rationally simultaneously. Results suggest that imposing a switch between intuition and rationalization thinking approach, via experimental instructions, improves creative ideation. Theoretical and practical implications are discussed.